Transient IR (0001–0000) absorption spectroscopy of optically centrifuged N2O with extreme rotation up to J = 205. (May 2020) - Ogden, Hannah M.; Michael, Tara J.; Murray, Matthew J.; Mullin, Amy S.
Highlights: High-resolution transient IR absorption spectroscopy was used to measure (00°1− 00°0) R-branch transition frequencies for N2 O molecules in extreme rotational states, with quantum number up to J  = 205 and energies as high as E rot =17, 000 cm −1 . A population inversion of rotationally excited N2 O states was prepared with an optical centrifuge and probed in a multi-pass IR cell using a quantum cascade laser. The optical centrifuge is based on 800-nm ultrafast, chirped laser pulses that optically trap molecules and accelerate them angularly to extreme rotational states. This work substantially increases the range of observed transitions for this band beyond J  = 100 transitions previously reported and provides benchmark measurements for theoretical predictions based on a polyad model of effective Hamiltonian. Transient Doppler-broadened IR line profiles of N2 O show that optical excitation of the sample is selectively partitioned into rotation, prior to doppler broadening from rotation-to-translation collisional energy transfer. These results demonstrate how high- J transitions can be measured without thermal heating by coupling optical centrifuge excitation with high-resolution transient IR absorption probing. Abstract: High-resolution transient IR absorption spectroscopy was used to measure (00 0 1− 00 0 0) R-branch transition frequencies for N2 O molecules in extreme rotational states, with quantum number up to J  = 205 and energies as high as E rot =17, 000 cm −1 . A population inversion of rotationally excited N2 O states was prepared with an optical centrifuge and probed in a multi-pass IR cell using a quantum cascade laser. The optical centrifuge is based on 800-nm ultrafast, chirped laser pulses that optically trap molecules and accelerate them angularly to extreme rotational states. This work substantially increases the range of observed transitions for this band beyond the J  = 100 transitions previously reported and provides benchmark measurements for theoretical predictions based on an effective Hamiltonian using a polyad model. Transient Doppler-broadened IR line profiles of N2 O show that optical excitation of the sample is selectively partitioned into rotation, prior to Doppler broadening from rotation-to-translation collisional energy transfer. These results demonstrate how high- J transitions can be measured without thermal heating by coupling optical centrifuge excitation with high-resolution transient IR absorption probing.